Cerebrospinal Fluid Homovanillic and 5-Hydroxyindoleacetic Acids in a Large Pediatric Population; Establishment of Reference Intervals and Impact of Disease and Medication. - Rodriguez-Gonzalez, Helena; Ormazabal, Aida; Casado, Mercedes; Arias, Angela Y; Oliva, Clara; Barranco-Altirriba, Maria; Casadevall, Ricard; García-Cuyas, Francesc; Nascimento, Andrés; Ortez, Carlos; Benito, Daniel Natera-de; Armangué, Thais; et al. (Clinical Chemistry, 2024)
Background Cerebrospinal fluid (CSF) homovanillic (HVA), and 5-hydroxyindoleacetic acids (5-HIAA) are biomarkers of neurological diseases affecting the dopaminergic and serotoninergic pathways. Establishing reference intervals for these metabolites faces the challenges of a lack of healthy controls and a negative correlation with age, making stratified intervals unrealistic. We propose a pipeline to determine continuous reference intervals for HVA and 5-HIAA using an indirect method. We also studied the confounding effects of different variables and explored the impact of antiepileptic and neuroleptic treatments on HVA and 5-HIAA values. Methods The study used least squares regression to fit age–concentration curves from a cohort of pediatric patients (n = 1533), where the residuals represent metabolite values excluding age effect. Presuming that HVA and 5-HIAA primary deficiencies characterize a distinct subpopulation, we fitted a two-component finite mixture model in age-normalized data and set reference intervals at the central 95% of the nondeficient population. Results Patients with primary genetic deficiencies of HVA and/or 5-HIAA consistently fall outside the proposed continuous reference intervals. Using the new continuous reference intervals reduces the number of secondary deficiencies detected compared with using stratified values. No correlations were observed between CSF HVA and 5-HIAA values across the studied drug categories (antiseizure and neuroleptic medications). In addition, biopterin values positively influenced both metabolite concentrations. Conclusion The proposed continuous reference intervals caused a substantial reduction in the number of secondary deficiencies detected, most of which demonstrated no conclusive correlations between the diseases and altered HVA and 5-HIAA values.